From keeping ‘nature’s secrets’ to the institutionalization of ‘open science’ - David, PA (University of Oxford, 2001)
This essay examines the economics of patronage and the roles of asymmetric information and reputation in the early modern reorganization of scientific activities, specifically their influence upon the historical formation of key elements in the ethos and organizational structure of publicly funded open science. The emergence during the late 16th and early 17th centuries of the idea and practice of 'open science' represented a break from the previously dominant ethos of secrecy in the pursuit of 'Nature's Secrets.' It was a distinctive and vital organizational aspect of the Scientific Revolution, from which crystallized a new set of norms, incentives, and organizational structures that reinforced scientific researchers' commitments to rapid disclosure of new knowledge. The rise of 'cooperative rivalries' in the revelation of new knowledge, is seen as a functional response to heightened asymmetric information problems posed for the Renaissance system of court-patronage of the arts and sciences; pre-existing informational asymmetries had been exacerbated by increased importance of mathematics and the greater reliance upon sophisticated mathematical techniques in a variety of practical contexts of application. Analysis of the court patronage system of late Renaissance Europe, within which the new natural philosophers found their support, points to the significance of the feudal legacy of fragmented political authority in creating conditions of 'common agency contracting in substitutes.' These conditions are shown to have been conducive to more favorable contract terms (especially with regard to autonomy and financial support) for the agent-client members of western Europe's nascent scientific communities.